The effectiveness of filters on catfish Clarias gariepinus fry performance in the aquaponic system - Andriani, Yuli; Hasan, Zahidah; Zidni, Irfan; Nurruhwati, Isni; Iskandar, Iskandar; Kusumoputra, Rahmadi (Jurnal Akuakultur Indonesia, 2021)
This study aimed to determine the effectiveness of filters on the growth performances of catfish fry (Clarias gariepinus) in the aquaponic system. The study was conducted in the Ciparanje Green House, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran, Jatinangor. A completely randomized design with four treatments and three replications was applied, namely treatment A: Water circulation using bioball filter medium, B: Water circulation using water spinach filter medium, C: Water circulation using bioball and water spinach filter media, and D: Water circulation using sponge filter medium (control). The container used for the maintenance was a fiber tank at 70 cm × 70 cm × 70 cm size filled with 257 L water and a stocking density of 15 fish/fiber. The parameters observed were survival rate, growth, feed conversion, and water quality. The results showed that the use of biological filter using water spinach produced the best growth performance of catfish. The best survival rate was also obtained by using water spinach filter (100%) with the absolute growth of 98.32 ± 15.6 g. The water quality an aquaponic system with water spinach filter supported the growth performance of catfish fry. Keywords: absolute growth, aquaponic, Clarias gariepinus, filters. ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas filter terhadap performa pertumbuhan benih ikan lele Clarias gariepinus dalam sistem akuaponik. Penelitian dilakukan di Laboratorium Rumah Kaca Ciparanje, Fakultas Perikanan dan Ilmu Kelautan, Universitas Padjadjaran, Jatinangor. Metode penelitian adalah rancangan acak lengkap dengan empat perlakuan dan tiga ulangan, yaitu perlakuan A: sirkulasi menggunakan media filter bioball, B: Sirkulasi menggunakan media filter bayam air, C: Sirkulasi menggunakan media filter bioball dan tanaman kangkung, dan D : Sirkulasi menggunakan media spons (kontrol). Wadah yang digunakan untuk pemeliharaan bak fiber dengan ukuran 70 cm × 70 cm × 70 cm diisi dengan air sebanyak 257 L dengan padat tebar 15 ekor / bak. Parameter yang diamati adalah kelangsungan hidup, pertumbuhan ikan, konversi pakan dan kualitas air. Hasil penelitian menunjukkan bahwa penggunaan filter biologis menggunakan tanaman kangkung menghasilkan performa pertumbuhan ikan lele yang terbaik. Tingkat kelangsungan hidup terbaik juga ditunjukkan oleh pelakuran dengan filter berupa tanaman kankung (100%) dan pertumbuhan mutlak 98,32 ± 15,6 g. Kualitas air sistem akuaponik dengan filter tanaman kangkung mendukung performa pertumbuhan benih ikan lele.